Sharing the Heritage of the Simalungun Batak Community: Realities and Implications - Muhammad Zuhirsyan; Pagar Pagar; Ansari Yamamah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
This study aims to determine the pattern of implementation of the distribution of inheritance by the Muslim community of the Simalungun Batak tribe in North Sumatra in terms of the reality and implications involved. The research model in this study is qualitative, while the approaches used are fiqh muamalah and family law approaches. Data were obtained from in-depth interviews and field observations by observing the application of inheritance law in the Muslim community of the Simalungun Batak Tribe then analyzing the pattern of distribution and utilization of inheritance. The results of this study indicate variations in the pattern of implementation of the distribution of inheritance carried out by the Muslim community of the Simalungun Batak Tribe in North Sumatra. Some people are reluctant to sell heritage assets and choose to keep them to preserve culture. Some choose the inheritance distribution based on faraid law, deliberation, fair distribution, or rely on the provisions given by their parents during their lifetime. The division through deliberation can be done if it is not intended to conflict with Islamic inheritance law. It is also possible to divide the share for each heir with an equal share if it follows the instructions of the Islamic Compilation Law and takharruj instructions.